Customized On-site Resource Training Services (CORTS) A Partnership Program. - Macquarie Univ., North Ryde (Australia). Special Education Centre; Macquarie Univ., North Ryde (Australia). Special Education Centre ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
In 1983, New Brunswick Community College-Moncton (NBCCM) was awarded funding to establish a Computer Aided Drafting/Manufacturing (CAD/CAM) resource center to train students and assist industry in researching and adopting CAD/CAM technology. However, inherent constraints in industry and the absorption of college resources by in-house training defeated the technology transfer purpose of the resource center. In 1988, NBCCM established the Customized On-Site Resource Training Services (CORTS) partnership program to provide customized, on-site training; consultation; assistance in database and prototype development; short-run production assistance; and financial assistance services at a minimum cost to small and medium-sized companies. CORTS enables the firms to invest in their human resources and also provides the "no risk-no cost" tools necessary for firms to evaluate the potential for integrating new technology in their operations. CORTS is run on a year-round basis and is completely self-supporting. Outcomes of the project include the following: (1) during its first full year of operation, more than 60 firms enrolled in the CORTS program, including 48 service firms that received CAD training/consultation and 15 manufacturers that received CAM assistance in prototype development and short-run production services; (2) a majority of the participating firms implemented CAD/CAM technology within their operations; (3) several firms amalgamated in order to share high-technology resources and bid on larger contracts; (4) additional staff were recruited by firms and NBCCM; (5) demand for the program in New Brunswick and other maritime provinces increased; and (6) NBCCM became the focal point for technology transfer and service to small regional businesses. Appendixes provide information on the status of CORTS programs and services, company testimonials, and additional documentation. (JMC)
Sponsoring Agency: New Brunswick Community Coll., Moncton.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Consultation Programs; Cooperative Programs; Inplant Programs; Labor Force Development; Manufacturing Industry; Outcomes of Education; Program Implementation; Research and Development; School Business Relationship; Small Businesses; Technical Assistance; Technological Advancement; Two Year Colleges; CAD CAM Programs; Reports, Descriptive